The Court of Appeal’s Decision in Muhamad Juzaili bin Mohd Khamis & Ors v State Government of Negeri Sembilan & Ors: A Real Breakthrough in the Law - bin Hairudin, Khairul Anwar; Qamar Siddique Bhatti, Saifullah Qamar (Journal of Malaysian and Comparative Law, 2018)
[W]e argue that the Court of Appeal’s judgment in Juzaili is all the more relevant today. It was the Navtej before Navtej. Its reversal by the Federal Court on appeal was erroneous. The judgment of the Court of Appeal ought to therefore remain law till today. We hope that judges in the future will be inspired to follow the precedent set by the Court of Appeal especially in developing jurisprudence in the field of privacy law. With respect, our judges have to be forward looking and consider the rights of individuals as a whole. They ought not to decide cases relating to fundamental liberties premised on what the society might think of them. The time to act is now. In the words of the majority in Navtej:39 [T]he constitutional courts have to embody in their approach a telescopic vision wherein they inculcate the ability to be futuristic and do not procrastinate till the day when the number of citizens whose fundamental rights are affected and violated grow in figures. Ultimately, whatever our moral convictions may be, the Federal Constitution remains supreme. It cannot be displaced by persons claiming to hold the moral torch.